(untitled) (Studia Politica. Romanian Political Science Review, 2025)
This article aims to analyze the rise and electoral success of the (Northern) League in Italy, for the period 2008-2018. The purpose of this analysis is to determine whether the economic difficulties encountered by the electorate or other factors, such as political and cultural ones, have influenced the growth and electoral success of the League in Italy. By analyzing both demand and supply-side data, the analysis shows that the League has had better electoral results in the years after the crisis when the economy has been improving than in the years when there has been a major economic shock. Regarding survey data on the supporters of the League, the analysis shows that the economy is among the least influential factors for them to support a right-wing populist party. On the contrary, the analysis shows that the main triggers for radical right populist mobilization have more to do with group values, identity issues, ethnic and cultural affiliation, xenophobic sentiments, skepticism towards foreigners, multiculturalism, and forms of Euroscepticism.